2016
DOI: 10.1371/journal.pone.0161858
|View full text |Cite
|
Sign up to set email alerts
|

MnemoCity Task: Assessment of Childrens Spatial Memory Using Stereoscopy and Virtual Environments

Abstract: This paper presents the MnemoCity task, which is a 3D application that introduces the user into a totally 3D virtual environment to evaluate spatial short-term memory. A study has been carried out to validate the MnemoCity task for the assessment of spatial short-term memory in children, by comparing the children’s performance in the developed task with current approaches. A total of 160 children participated in the study. The task incorporates two types of interaction: one based on standard interaction and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 47 publications
5
53
1
2
Order By: Relevance
“…The lower scores of the youngest participants suggest that their visuospatial short-term memory and/or their spatial strategies were relatively weaker during this developmental period. This result is consistent with previous studies (Bullens et al 2010;Purser et al 2012;Nys et al 2015;Mendez-Lopez, Perez-Hernandez, and Juan 2016;Merrill et al 2016) and with the results found by Rodríguez-Andrés et al (2016). They performed descriptive analyses taking into account the age of the participants and the VOL task score.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lower scores of the youngest participants suggest that their visuospatial short-term memory and/or their spatial strategies were relatively weaker during this developmental period. This result is consistent with previous studies (Bullens et al 2010;Purser et al 2012;Nys et al 2015;Mendez-Lopez, Perez-Hernandez, and Juan 2016;Merrill et al 2016) and with the results found by Rodríguez-Andrés et al (2016). They performed descriptive analyses taking into account the age of the participants and the VOL task score.…”
Section: Discussionsupporting
confidence: 92%
“…The present task assessed not only the ability of the children to recall the place of the objects, but also their way of exploring the interaction area of the VE. The aims of the study by Rodríguez-Andrés et al (2016) were mainly to present the task, to validate the task for the assessment of spatial shortterm memory, and to examine the influence of the type of interaction used on the ability to recall the place of the objects, and the perceived usability and satisfaction of the children with the task.…”
Section: Discussionmentioning
confidence: 99%
“…Juan et al [46] found similarities in the results using ARSM Task and traditional methods. MnemoCity Task [48] had a virtual reality environment, with passive stereoscopy and natural interaction to evaluate spatial memory in children. The study compared two types of interaction: 1) a gamepad; 2) a steering wheel (with a built-in Wii Remote TM control) and Wii Balance Board TM .…”
Section: Assessment Of Spatial Memorymentioning
confidence: 99%
“…NUI are being incorporated in different types of applications, for example, learning [3], assessment of shortterm memory [4]; training individuals with cognitive impairments [5]; or transforming a paper based process to a NUI process in a chronic care hospital [6].…”
Section: Introductionmentioning
confidence: 99%